1999
DOI: 10.1046/j.1365-2699.1999.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Competition, coexistence, and adaptation amongst rodent invaders to Pacific and New Zealand islands

Abstract: Summary Variation in skull size was investigated for three species of rats (kiore –Rattus exulans Peale; ship rat –R. rattus L.; Norway rat –R. norvegicus Berkenhout) which were introduced by humans to various islands in New Zealand and other Pacific islands. Data from seventy‐one islands and 882 specimens are examined for evidence of the effects of latitude, island size and interspecific competition among rats and the house mouse (Mus musculus L.) on skull size, using multiple regressions. For R. exulans, sku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 50 publications
6
95
2
Order By: Relevance
“…These Pacific-wide R. rattus body size measurements were similar to those summarized across New Zealand (Innes 2005a). Unlike other invasive Rattus species ( YomTov et al 1999, Atkinson andTowns 2005), there does not appear to be a Pacific-wide pattern of greater body size with increasing latitude for R. rattus ( Yom-Tov et al 1999; A.B.S., J. Russell, and W.C.P., unpubl. data).…”
Section: Species Descriptionsupporting
confidence: 77%
See 1 more Smart Citation
“…These Pacific-wide R. rattus body size measurements were similar to those summarized across New Zealand (Innes 2005a). Unlike other invasive Rattus species ( YomTov et al 1999, Atkinson andTowns 2005), there does not appear to be a Pacific-wide pattern of greater body size with increasing latitude for R. rattus ( Yom-Tov et al 1999; A.B.S., J. Russell, and W.C.P., unpubl. data).…”
Section: Species Descriptionsupporting
confidence: 77%
“…All teeth grow continuously throughout life, and the large incisors, which are specialized for gnawing and grinding, must be kept to a usable length by grinding and self-sharpening (Innes 2005a). The skull is also specialized for gnawing, and the average length of R. rattus skulls in the Pacific region is 40 -43 mm ( Yom-Tov et al 1999). Because of the size variability across ages, the size of R. rattus droppings (6.8 -13.8 mm) cannot always be used to distinguish the species from other species of common invasive rats (Atkinson and Towns 2005).…”
Section: Species Descriptionmentioning
confidence: 99%
“…Ship rats on islands were heavier and larger (Yom-tov et al 1999) than on mainland New Zealand which supports the micro-evolutionary portion of the theory, probably because a large suite of competitors and predators were absent (Adler & Levins 1994;Yom-tov et al 1999;Ventura & Lopez Fuster 2000). Rapid morphological responses in rodents and other small mammals to changing ecological conditions are now well recorded (Pergams & Ashley 2001;Pergams & Lawyer 2009;Cucchi et al 2014).…”
Section: Discussionmentioning
confidence: 62%
“…Much evidence points to the largest of the three rodents, the black rat, as the dominant competitor of the three species studied (Yom-tov et al 1999;Russell and Clout 2004;Shiels 2010). Stokes et al (2009) in Australia, and Harris and Macdonald (2007) in the Galápagos Islands, demonstrated that native rats (R. fuscipes and Nesoryzomys swarthi, respectively) suffered from interference competition rather than resource competition with the larger, non-native black rats.…”
Section: Discussionmentioning
confidence: 99%